2020
DOI: 10.3390/genes11030339
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evolution of Legume Symbionts: What Have We Learnt?

Abstract: Rhizobia, the nitrogen-fixing symbionts of legumes, are polyphyletic bacteria distributed in many alpha- and beta-proteobacterial genera. They likely emerged and diversified through independent horizontal transfers of key symbiotic genes. To replay the evolution of a new rhizobium genus under laboratory conditions, the symbiotic plasmid of Cupriavidus taiwanensis was introduced in the plant pathogen Ralstonia solanacearum, and the generated proto-rhizobium was submitted to repeated inoculations to the C. taiwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 170 publications
(233 reference statements)
2
17
0
Order By: Relevance
“…Questions that remain for the future are the determination of how competitive the TER strains are in the presence of other nodulating strains, and the isolation of the putative recipients, which would be very helpful to determine the scope of possible transfers. Recently, Doin de Moura et al (2020) introduced the symbiotic plasmid of Cupriavidus taiwanensis into the plant pathogen Ralstonia solanacearum , and repeatedly inoculated the C. taiwanensis host, Mimosa pudica with the transconjugant. This experimental evolution allowed for the selection of derivatives able to nodulate and improve efficiency after various passages through the plant.…”
Section: Discussionmentioning
confidence: 99%
“…Questions that remain for the future are the determination of how competitive the TER strains are in the presence of other nodulating strains, and the isolation of the putative recipients, which would be very helpful to determine the scope of possible transfers. Recently, Doin de Moura et al (2020) introduced the symbiotic plasmid of Cupriavidus taiwanensis into the plant pathogen Ralstonia solanacearum , and repeatedly inoculated the C. taiwanensis host, Mimosa pudica with the transconjugant. This experimental evolution allowed for the selection of derivatives able to nodulate and improve efficiency after various passages through the plant.…”
Section: Discussionmentioning
confidence: 99%
“…• Modified Ralstonia solanacearum evolving in a plant symbiont (Marchetti et al, 2010;Doin de Moura et al, 2020)…”
Section: Experimental Evolution To Decipher the Adaptive Evolution Of Single Microbial Population In Synthetic Systems Of Low Complexitymentioning
confidence: 99%
“…Legumes are characterized by the ability to form nodules that house endosymbiotic rhizobia. This relationship generates a driving force between the two symbionts that leads them to co-evolve [90,91]. It has been reported that plant lipochitooligosaccharide receptors acquired symbiotic functions before gene duplication [92].…”
Section: Differences and Similarities In The Expression Of Crrlk1l Gementioning
confidence: 99%